Analysis of Teacher Performance Innovation Through Innovative Learning Strategy In The Era of Industrial Revolution 4.0 - Muliati Usman; Fadhilah Fadhilah (Proceedings of AICS - Social Sciences, 2021)
The Industrial Revolution 4.0 leads to innovation in all aspects including education. In this era, teachers need to adapt to change by using technological advances to support teachers' innovation. This study analyzed that innovative learning strategy through cyber technology improves teacher performance innovation in the era of Industrial Revolution 4.0. However, the application of innovative learning strategies through cyber technology for students will not be successfully applied in learning without the support or guidance of the teacher. The teacher's role as a mentor cannot be replaced by cyber technology. Therefore, Blended Learning is the most appropriate model in implementing innovative learning strategies in the era of Industrial Revolution 4.0. It is a combination or integration of cyber technology and teacher as adviser or motivator. Blended Learning is an interesting learning system that motivates students in learning that focuses on creativity and student participation. While, contributions from all parties are needed to prepare teachers as human capital who are ready to adapt the industrial revolution 4.0 through various education or training programs.Keywords: Innovation Performance, Innovative Learning Strategy, Blended Learning,Teacher Competence